1990
DOI: 10.1017/cbo9780511752803
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Violence

Abstract: The author examines criminal behaviour from birth to adulthood in a sample of nearly 1,000 subjects in order to determine the biological and sociological influences on violence. Over 100 predictors of violent behaviour found to be significant in past biological and sociological studies of crime are analysed. The results indicate that both biological and environmental factors produce strong, and independent, effects on both delinquency and adult crime and violence among both males and females. Powerful influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(36 citation statements)
references
References 0 publications
3
30
0
3
Order By: Relevance
“…There is also substantial evidence linking preschool lead exposure to crime and other behaviors that impose substantial societal costs (Denno 1990, Dietrich et al 2001, Needleman et al 1996, Nevin 2000. While other factors also contribute to criminal behavior, juvenile delinquency and other anti-social behaviors, lead exposure consistently emerges as one of the significant independent variables involved.…”
Section: Other Health Benefits From Lead-safe Window Replacementmentioning
confidence: 99%
“…There is also substantial evidence linking preschool lead exposure to crime and other behaviors that impose substantial societal costs (Denno 1990, Dietrich et al 2001, Needleman et al 1996, Nevin 2000. While other factors also contribute to criminal behavior, juvenile delinquency and other anti-social behaviors, lead exposure consistently emerges as one of the significant independent variables involved.…”
Section: Other Health Benefits From Lead-safe Window Replacementmentioning
confidence: 99%
“…The significance of environmental toxins is that they can and do change behavior, and that part of that change in behavior can produce crime and delinquency (Denno, 1990;Raine, 1993). While the precise pathway of that effect has scientific importance, establishing the pathway's effects is presupposed by green behaviorism-that is, the scientific basis for the effect is established in other disciplines-and its reliance on prior scientific findings related to these outcomes.…”
Section: Does the Biological Pathway Matter?mentioning
confidence: 99%
“…In addition to many other adverse health effects, recent research has shown that even blood lead levels below 10 µg/dL in early childhood may be associated with intellectual impairment FANNIE MAE FOUNDATION (Canfield et al 2003). Other research has shown that exposure to lead in early childhood has a strong association with delinquent and criminal behavior among juveniles and young adults (Denno 1990;Dietrich et al 2001;Needleman et al 1996;Nevin 2000).…”
Section: The Risk To Children From Exposure To Leadmentioning
confidence: 99%